Effect of organic fertilizer and its residual on cowpea and soybean in acid soils - Henny Kuntyastuty; Siti Muzaiyanah (Brawijaya University, 2017)
The expansion of planting areas on acid soils is one of the strategies to achieve Indonesian self-sufficiency program on food. Acidic soil has low pH that causes contents of Al, Fe, and Mn are high. In addition, acidic soil also only has low microbial population. These conditions make soybean growth is not optimal. This research consisted of two phases i.e., the first and second planting. The first planting was aimed to study the effectiveness of fertilizer treatment, with three replications, using cowpea commodity. The second planting was done without additional fertilizer that consisted of three replicates (continued from the first planting) using soybean. This research that was carried out at Iletri’s greenhouse Malang in 2014 was arranged in a randomized block design consisting of eight treatments, namely: (a) control/without fertilizer; (B) 300 kg/ha (15% N, 15% P2O5, 15% K2O, 10% S); (C) 1500 kg/ha cow manure; (D) 3000 kg/ha cow manure; (E) 5000 kg/ha cow manure; (F) 1500 kg/ha fermented chicken + cow manures; (G) 3000 kg/ha fermented chicken + cow manures; and (H) 5000 kg/ha fermented chicken + cow manures. The results showed that organic fertilizer (cow manure) 5000 kg/ha had higher yields both in the first planting and second planting compared to inorganic fertilizer 300 kg/ha (15% N, 15% P2O5, 15% K2O, 10% S)